2009
DOI: 10.1002/path.2516
|View full text |Cite
|
Sign up to set email alerts
|

Syndromic and non‐syndromic aneurysms of the human ascending aorta share activation of the Smad2 pathway

Abstract: Common features such as elastic fibre destruction, mucoid accumulation, and smooth muscle cell apoptosis are co-localized in aneurysms of the ascending aorta of various aetiologies. Recent experimental studies reported an activation of TGF-beta in aneurysms related to Marfan (and Loeys-Dietz) syndrome. Here we investigate TGF-beta signalling in normal and pathological human ascending aortic wall in syndromic and non-syndromic aneurysmal disease. Aneurysmal ascending aortic specimens, classified according to ae… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
121
6
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 165 publications
(140 citation statements)
references
References 52 publications
11
121
6
2
Order By: Relevance
“…26 Conversely, ACTA2/MYH11 mutations affect the contractile apparatus of the vascular smooth muscle cells rather than TGF-β1 signaling. Therefore, lower TGF-β1 levels may be expected from the underlying major pathomechanism despite some evidence for upregulation of TGF-β1 signaling in ACTA2 and MYH11 mutations with TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…26 Conversely, ACTA2/MYH11 mutations affect the contractile apparatus of the vascular smooth muscle cells rather than TGF-β1 signaling. Therefore, lower TGF-β1 levels may be expected from the underlying major pathomechanism despite some evidence for upregulation of TGF-β1 signaling in ACTA2 and MYH11 mutations with TAAD.…”
Section: Discussionmentioning
confidence: 99%
“…1, 8 Indeed, several lines of evidence indicate augmented TGF-b signalling in aortic lesions in vivo. 6,9,10 This is intriguing as many pathogenic mutations associated with TAAD have a loss-of-function effect. 2,11,12 Recently, two studies have shown that haploinsufficiency for TGFB2 causes a familial syndrome of TAAD with additional clinical manifestations overlapping MFS and LDS.…”
Section: Introductionmentioning
confidence: 99%
“…Dysregulation of the TGF-β signaling pathways is seen in other aneurysmal diseases including Marfan syndrome, owing to a mutation of the FBN1 gene, and Loeys-Dietz syndrome, through a mutation of the TGFB2 gene 4 .…”
Section: To the Editormentioning
confidence: 99%